Control System for Security Enhancement of CCTV Camera Maintenance Devices - Moon, Chaeyoung; Ryoo, Kwangki (International Journal of Engineering and Technology, 2018)
Background/Objectives: Automatic lift systems are used for the convenient and safe maintenance of CCTV cameras installed in high places. However, the control unit is often installed in an area easily accessible by outsiders, and this may lead to camera manipulation by an unauthorized person.Methods/Statistical analysis: To maintain the existing control unit and enhance its security, first, the control button for the ALS located inside the control unit needs to allow input signals only upon approval by the control center. Second, the program for ALS control should be added to the installed NVR for image storage purposes. Finally, an algorithm for encrypted key generation needs between the Network Video Recorder and ALS to enhance the security and reliability.Findings: To address these issues, this study designed a control system that offers enhanced security for an automatic lift system by enabling system control in a control tower. The server of the control system only approved requests by authorized persons for any operations. In addition, the system was designed to monitor the surrounding environments of all CCTV cameras within the operation area. Through these functions, the system was able to detect a fire, a gas leak, fine dust concentration levels, etc. within the surveillance area to ensure the safe maintenance of facilities.Improvements/Applications: This control system is expected to enhance the security of CCTV systems used for the surveillance of key facilitiesÂ